The prevalence of tuberculosis, malaria and soil-transmitted helminth infection in minority indigenous people of Southeast Asia and the Western Pacific: protocol for a systematic review and meta-analysis - Gilmour, Beth; Alene, Kefyalew; Clarke, N.E.; Clements, Archie C.A. (BMC, 2021)
Background: Infectious diseases such as tuberculosis (TB), malaria and soil-transmitted helminthiasis continue to impose a significant global health burden and socio-economic impact. Globally, minority indigenous people are disproportionately affected by poverty and are shown to experience a disparate burden of disease and poorer health outcomes than the comparative majority population. Despite these inequalities, countries rarely systematically compile epidemiological data disaggregated by ethnicity to enable the extent of the differential to be quantified.